MODEL PEMBIAYAAN MIKRO PADA MAHASISWA BERBASIS ENTREPRENEURSHIP - Aisyah, Esy Nur; Solekah, Nihayatu Aslamatis (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
The economic activities of society and the economy as a whole can not be separated from both conventional and shariah banking and the role of small and medium enterprises. To improve the entrepreneur's soul need a new breakthrough to improve the entrepreneurship spirit from the start to the students in running the business. However, the provision of credit for entrepreneurs, especially students who have interest in entrepreneurship has almost never been done formally, considering many factors such as for security and loans. The focus in this research is how the micro-finance model for entrepreneurship-based students at El Dinar Finance House. The purpose of this study provides a model of micro-financing (revolving funds) for entrepreneurship-based students at El Dinar Fiannce House, so as to increase the entrepreneurial spirit of students in running a business with the aim to create jobs and reduce the number of unemployed. In the program of revolving fund financing for students, El-Dinar Finance House is able to provide services required by students, but in this case, el El-Dinar Finance House is not only limited to funding but also must be able to monitor/accompany finance customers until repayment . So in this case El-Dinar Finance House able to provide a model of assistance for financing customers with the aim of achieving an effective and efficient economic cycle.